THE JURY TRIAL IN UKRAINE: PROBLEMS OF THEORY AND PRACTICE - Логвиненко, Аліса Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: the article examines the legal status of the jury trial in Ukraine. The views of scientists concerning the existence of such institute are analyzed. Methods: the list of normative acts in this area is defined. The foreign experience of creating a institution of jury is analyzed. Results: the problems of the functioning of the jury trial in Ukraine and identified ways to further reform are analyzed. Discussion: amending the legislation on this issue.